Impact of Health Practitioners on Mental Health: A Comprehensive Review - Saleh Radhi A et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Mental health is a critical component of overall well-being, and health practitioners play a pivotal role in its promotion, prevention, diagnosis, and treatment. This review explores the multifaceted impact of health practitioners on mental health, focusing on their roles in providing care, reducing stigma, and enhancing accessibility to mental health services. Furthermore, it highlights the challenges practitioners face, including inadequate training, resource constraints, and high levels of burnout. Emerging evidence underscores the effectiveness of practitioner-led interventions in improving mental health outcomes, particularly when employing multidisciplinary and culturally sensitive approaches. This review aims to provide insights into the contributions and challenges faced by health practitioners in the mental health domain, offering recommendations for improving their impact. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/271 https://doi.org/10.5281/zenodo.14480307